2016
DOI: 10.1007/s13187-016-0984-7
|View full text |Cite
|
Sign up to set email alerts
|

Racial Disparities in Emotional Distress Among Cancer Survivors: Insights from the Health Information National Trends Survey (HINTS)

Abstract: The purpose of this study was to examine the impact of race, cancer history, and their interaction on emotional distress among a nationally representative sample of US adults. Data utilized for this analysis were obtained from the first, second, and fourth iterations of the fourth cycle of the Health Information National Trends Survey (HINTS). The study sample included 3959, 3630, and 3677 respondents for the years 2011, 2012, and 2014, respectively, for a total sample size of 11,266. A multivariable ordered l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 41 publications
1
17
0
Order By: Relevance
“…These variables were chosen "a priori" on the basis of the literature demonstrating a relationship between these variables and depressive symptoms. [29][30][31][32][33][34] Case-wise deletion was used for missing values.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These variables were chosen "a priori" on the basis of the literature demonstrating a relationship between these variables and depressive symptoms. [29][30][31][32][33][34] Case-wise deletion was used for missing values.…”
Section: Discussionmentioning
confidence: 99%
“…Predictor variables included age, gender, race, ethnicity, cancer type, and marital/living status. These variables were chosen “a priori” on the basis of the literature demonstrating a relationship between these variables and depressive symptoms . Case‐wise deletion was used for missing values.…”
Section: Methodsmentioning
confidence: 99%
“…10,[27][28][29][30] However, many of these studies were restricted to only one specific cancer site and thus did not include a diverse sample of diagnoses, 22,24,25,27,29,31 or focused only on long-term survivors who were no longer receiving cancer treatment. 21,27 Additionally, only 5-25% of participants in these studies were African American, so inconsistent findings may have been attributed to sampling bias or a lack of power. Moreover, studies that included disproportionately low numbers of African American patients are less generalizable to individuals in Louisiana, which includes a larger proportion of African American patients compared to most other states.…”
Section: Introductionmentioning
confidence: 91%
“…However, existing research of racial disparities in cancer-related distress is limited to studies that were conducted outside of Louisiana, and methodological issues in these studies impede the ability to identify clear patterns in findings. Some studies have found that African Americans were more likely than White patients to experience distress, [20][21][22][23] whereas others found that African Americans were less likely to have distress, [24][25][26][27] or that there was no significant association between race and distress. 10,[27][28][29][30] However, many of these studies were restricted to only one specific cancer site and thus did not include a diverse sample of diagnoses, 22,24,25,27,29,31 or focused only on long-term survivors who were no longer receiving cancer treatment.…”
Section: Introductionmentioning
confidence: 99%
“…The Health Information National Trends Survey (HINTS) study has found that African American survivors report higher levels of distress compared to other survivors and non-cancer controls. 55 Gay and bisexual prostate cancer survivors also report more distress than heterosexual prostate cancer survivors. 56 Married prostate cancer survivors with lower levels of partner support and unmarried survivors reported more distress than married survivors with high levels of partner support.…”
Section: Anxiety and Depression In Different Populations Of Survivorsmentioning
confidence: 98%